Assessment of Stroke Severity And Mortality (ASSAM): A hospital-based study from north-east India - Glennys Carvalho; Debabrata Goswami; Abdul Barik Ahmed (Indian Journal of Community and Family Medicine)
Background: Stroke burden continues to grow; ischemic subtypes share the biggest pie. Assam is one of the states with the highest burden in-terms of mortality. Aim: In Assam, we studied factors operating at different timelines concerning stroke events in 119 stroke patients to identify entry points for policy-level interventions. Material and Methods: We used the National Institute of Health Stroke Score (NIHSS) at admission to assess stroke severity and the Modified Rankin Scale and Barthel Index of activities of daily living at discharge and day 30 after onset to study the functional outcomes. Mortality data were captured until day 30 of stroke onset, and epidemiological data on risk factors and other determinants was collected using a questionnaire. Results: In our study, the majority (55.5%) of patients admitted with stroke were in the age group of 51–70 years, while 9.2% were below 40 years. Only 2.5% of cases reached the hospital within 4.5 h; about 42% had multimorbidity. Hypertension was a major risk factor along with dyslipidemia. Nearly 18% had wake-up strokes, and a similar proportion had a cerebrovascular event in the past. Those with higher NIHSS scores had a higher risk of dying, and if they survived, they had a higher risk of poor functional outcomes at day 30. Women experienced a higher proportion of mortality than men and more so during the posthospitalization period. Conclusion: The epidemiological data obtained from this study helps provide insights into some of the determinants in the pre- and post-period of the stroke event, especially in resource-limited areas; as a part of ongoing surveillance, such data can help monitor temporal trends.